The influence of electronic words of mouth (eWOM) on the Malay film industry / Abdul Aziz Azizam - Azizam, Abdul Aziz (2014)
The growth of the Malay film industry in Malaysia nowadays has rapidly increased. This phenomenon occurs due to the popular demand by the Malaysian audience. eWOM also is seen as an effective tool that may help cater to the demand. Recently, many Malay films are able to compete with the Hollywood movies in terms of box office collection. One of the reasons is that, Malay industry has discovered the sequences of innovative technologies such as CGI (Computer Generated Imagery), Green Screen, and also eWOM. The electronic words of mouth or (eWOM) has become one of the most popular topics in the current local film industry. In Malaysia, the development of the Malay films can be seen as a considerable effect of eWOM. However, there are still a minimum number of studies conducted in Malaysia regarding the influence of eWOM towards film, especially the Malay film production. Hence, the aims of this study are to understand the function of eWOM, to explore whether eWOM is a better influence in Malay film marketing rather than the traditional Malay film promotions, and to study how eWOM influences the Malay film industry that underwrites the development of the Malay film industry. This study is an exploratory study, and researcher used qualitative-grounded theory approach to accumulate the data through several focus group sessions as the main data along with triangulation with in-depth interview and also content analysis to ensure the credibility of the data. By using the grounded theory design, the researcher generated a middle-range conceptual model to provide further understandings regarding the effects of eWOM to Malay film industry.